Hubungan Alignment Knee Joint terhadap Kecepatan Berlari pada Anak Usia 4-6 Tahun - Haura, Rifka Alifia; Miranti Yolanda Anggita; Abdul Chalik Meidian (Jurnal Fisioterapi Terapan Indonesia, 2025)
Alignment Knee joint alignment is a critical component in the biomechanical analysis of the body, particularly in locomotor activities such as running. Imbalance or malalignment in the knee joint can disrupt movement patterns and increase the risk of musculoskeletal injuries. In pediatric physiotherapy, early identification of lower limb posture is essential to support optimal gross motor development. This study aims to examine the relationship between knee joint alignment and running speed in children aged 4–6 years. A crosssectional design was used, involving 45 children who met the inclusion criteria. Measurement of knee alignment was performed using a goniometer to assess the quadriceps angle (Q-angle), and running speed was evaluated using a 20-meter sprint test. Statistical analysis with Spearman’s correlation revealed a significant relationship (p=0.012; r=0.373). These findings indicate that better knee joint alignment is associated with faster running speed in young children. This study underscores the importance of biomechanical evaluation in physiotherapy interventions for early childhood development.